Electronic and photophysical properties of copper (II) Complexes: Insights into solvatochromic Effects, Photoreduction, and fluorescence behavior - Haja Tar; Lama M. Alhomaidan; Lotfi Beji; Abrar S. Alnafisah; Noura Kouki; Sabri Messaoudi; Fahad M. Alminderej; Azizah A. Algreiby; Lotfi M. Aroua (Results in Chemistry)
This study delves into the intricate electronic and photophysical properties of copper (II) complexes and their ligands, shedding light on their behavior under varying conditions. UV–Vis absorption spectroscopy unveils significant insights, revealing absorption peaks attributed to ligand–metal charge transfer transitions (LMCT) and π → π* transitions of C = N bonds. The solvent’s polarity dictates the absorption peak positions, indicating a pronounced solvatochromic effect. Molar extinction coefficients underscore the complexes’ high absorption efficiency across different solvents. Density Functional Theory (DFT) calculations provide a theoretical framework, elucidating electronic transitions observed experimentally. While HL1 exhibits a single peak, HL2 displays two peaks, findings supported by calculated transition energies and oscillator strengths.Moreover, the oxidation processes of copper complexes with iodide salt and triethylamine unveil favorable electron transfer mechanisms, as corroborated by cyclic voltammograms and free energy change values. Photolysis experiments underpin the complexes’ behavior under light irradiation, revealing reversible photoreduction processes and the formation of novel photoproducts. Notably, the addition of triethylamine influences photolysis kinetics, elucidating complex interactions. Furthermore, fluorescence experiments unveil the fluorescent behavior of bidentate copper (II) complexes and their ligands. Fluorescence emission peaks, observed around 475–550 nm for complexes and 400–550 nm for ligands, are influenced by solvent polarity, indicating solvent effects on fluorescence deactivation pathways. Overall, this comprehensive investigation provides valuable insights into the electronic and photophysical characteristics of copper (II) complexes, paving the way for their potential applications in diverse fields, including materials science, catalysis, and photochemistry.